Corrosion Behavior of ZnMn Coatings Magnetoelectrodeposited - Allam, Lamia; Lazar, Florica S.; Chopart, Jean-Paul (Magnetochemistry, 2022)
The zinc–manganese alloy coatings have been obtained without and with superimposition of a 0.3 T magnetic field in a parallel direction to the working surface electrode. The electrodeposition during 30 min, for two applied potentials (E = −1.6 V/SCE and E = −1.8 V/SCE) in an electrochemical bath with the (Zn2+)/(Mn2+) concentration ratio equal to 0.5. The structural, the morphological, and the chemical composition characteristics of the deposits have been studied. It has been found that the applied potentials modify the structural properties of the deposits, η phase-rich deposits elaborated for E = −1.6 V/SCE, and MnZn3-rich deposits elaborated for E = −1.8 V/SCE. The magnetohydrodynamic convection favors the manganese content of the deposit. The corrosion behavior of these coatings has been analyzed in 3.5% NaCl solution by free corrosion potential measurements and electrochemical impedance spectroscopy. The different results show that the corrosion resistance of these zinc–manganese alloy coatings is linked to their structure, to their composition, and to the magnetic field amplitude used during the electrodeposition process.
Number: 7
Keywords: EIS; MnZn_3; XRD; ZnMn alloys; corrosion; magnetic field; η phase